2017
DOI: 10.20959/wjpps20179-9951
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Benzene Extract of Abies Webbiana Lindl. (Fam-Pinaceae) Leaves

Abstract: The chemical diversity within the natural products is an immensely rich source of new pharmaceuticals, cosmetics and other economically important chemicals. Presently, numerous pure compounds are being isolated from plant sources having very promising therapeutic profiles. Now, the synthetic drugs are gradually sidelined by phytomedicines due to their adverse effects and the inability to provide complete cure in certain diseases and disorders in a cost effective manner. The present study was done to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…From phytochemical investigation, biologically active principles such as flavonoids, tannins, phenolic compounds, and phytosterols in plants are revealed. It is suggested that one of the above constituents or a combination is responsible for producing the analgesic and [53] anti-inflammatory effects. Few studies show that the anti-inflammatory property of A. webbiana might be due to flavonoids or even steroids that are present in them [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From phytochemical investigation, biologically active principles such as flavonoids, tannins, phenolic compounds, and phytosterols in plants are revealed. It is suggested that one of the above constituents or a combination is responsible for producing the analgesic and [53] anti-inflammatory effects. Few studies show that the anti-inflammatory property of A. webbiana might be due to flavonoids or even steroids that are present in them [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Anti inflammatory activity of A. webbiana has not been reported in many studies in literature. It was only studied on rats [53]. There are several other properties of A. webbiana such as antimicrobial and antitumor agents as well used in ayurveda [59].…”
Section: Discussionmentioning
confidence: 99%
“…The antiinflammatory effect was exhibited by pinitol which was isolated from the leaf. A new aziridine alkaloid was isolated from the leaves of A. webbiana [55]. Moreover, it has been reported that large number of different chemical compounds such as phenolic compounds and derivative compounds, the esters of weak acid, fatty acid, terpenes, and others are presented in ethanolic extracts of this plants and thus these chemical components can affect multiple target sites against the bacterial cells [56].…”
Section: From the Figure We Can Conclude That Anti-microbial Activity...mentioning
confidence: 99%